Inequalities in child injuries in Nepal: findings of a community based survey in Makwanpur. (7th October 2012) - Pant, PR; Towner, E; Ellis, M; Pilkington, P
Abstract : Background: The lack of data on prevalence, risk factors, costs and consequences of child injuries has led to a lack of awareness and understanding of the problem in low income countries. Aim: To investigate whether socio-economic status of families is associated with injury morbidity among children in rural Nepal. Results: A community based household survey was conducted in Makwanpur district, Nepal. Families of children with injuries, which required treatment or caused problems for at least 3 days, were interviewed. A total of 2868 households were analysed using Factor Analysis to create SES wealth status and the households were ranked into five quintiles. The relationship of wealth status with socio-economic and demographic characteristics will be presented. Findings: Only 6.3% (181) of survey households reported that a child was injured. Injured children disproportionately came from the lowest wealth quintiles. The ratio of lowest to highest quintiles was 1.37 (PCA). OR for the lowest SES quintile (1.27; 95% CI 0.78 to 2.06) when compared to the highest. OR for having 3–4 children per household (2.30; 95% CI 1.62 to 3.27) and for having 5 or more children per household (3.42; 95% CI 2.45 to 5.21) compared to 1–2 children per household; the second lowest and middle quintiles have highest injury risk. Having three or more children/household was found to be a risk factor for child injury. The ORs exhibit complex trends with increased SES levels. Significance: There are few examples of studies examining child injury and inequalities in low and middle income countries. There is a need to study inequalities in injury to help guide more effective prevention.